Christological Anthropology - Marc Cortez; Daniel Lee Hill (St Andrews Encyclopaedia of Theology, 2023)
Theologians have long maintained that Christology is vital for a properly theological understanding of the human person. Patristic theology maintained an intrinsic link between the humanity revealed in Christ and that which we ought to believe about humanity in general (Beeley 2016), an emphasis that was maintained by many in the medieval and Reformation eras as well (Cortez 2016). However, modern theology has witnessed a notable increase in the number of theologians arguing for more explicitly christological anthropologies (e.g. Rahner, Barth, and Balthasar), raising questions about what distinguishes a christological anthropology from a general theological approach to humanity, what reasons these theologians have for making this move, and what criticisms or challenges a christological anthropology needs to address if it is going to make a meaningful contribution to our understanding of humanity.